Prevalence of alcohol consumption among clients of opioid agonist treatment (OAT) centers in Golestan province, Iran - Noroozi, Alireza; Danesh, Ahmad (Frontiers in Psychiatry, 2023)
Introduction Opioid agonist treatments (OATs) with methadone and buprenorphine are known to be effective treatments for people with opioid use disorder (OUD). However, concomitant use of other substances such as alcohol can negatively affect OAT outcomes. This study aimed to determine the prevalence of alcohol use among clients of OAT centers in the Golestan province in the northern part of Iran. Materials and methods This is a secondary analysis of a sample of 706 clients who were receiving OATs from certified OAT centers in Golestan province in 2015. They had been on OATs for at least 1 month and were randomly selected for the study. Data were collected via interviews with selected OAT clients. The main indicators studied in the present study were lifetime history of alcohol consumption, alcohol consumption during last month, lifetime history of excessive alcohol use on one occasion, and years of regular alcohol consumption. Results The prevalence of lifetime history of alcohol consumption was estimated at 39.2%. Prevalence of alcohol consumption during last month and lifetime history of excessive alcohol use on one occasion was 6.9 and 18.8%, respectively. Conclusion Despite a total ban on alcohol consumption in Iran, a sub-sample of participants admitted past-month alcohol use concurrent with their OATs. The estimated past-month prevalence of alcohol use was lower than the reported prevalence in countries where the production, distribution, and consumption of alcohol are legal.